The Relationship between Internal Control Systems and Financial Reporting Scandals: Evidence from Nairobi Securities Exchange Listed Companies - Nkobe, Kenyoru; Mwaniki, Gillian; Omanwa, Clemence (International Journal of Professional Practice, 2026)
Despite extensive regulatory frameworks designed to prevent financial misconduct, accounting scandals continue to emerge globally, undermining investor confidence and market integrity. This study examines the relationship between Internal Control Systems (ICS) and financial reporting scandals among Nairobi Securities Exchange (NSE)-listed companies in Kenya. Using a census of all 62 NSE-listed companies, data were collected from 155 respondents, including accountants, internal auditors, finance officers, and company secretaries, through structured questionnaires. The study was anchored in the Fraud Triangle theory, which recognizes pressure, opportunity, and rationalization as essential elements of fraud. This research used descriptive statistics, correlation analysis, and regression analysis to examine the relationship between ICS and financial reporting. Results showed a robust positive correlation (r = 0.639, p < 0.001) between internal control systems and financial reporting quality. Regression analysis showed that ICS explains 40.8% of the variance in financial reporting practices (R² = 0.408, F = 104.441, p < 0.001), with a standardized coefficient (β = 0.639, p < 0.001). Findings demonstrate that stronger internal control systems are significantly associated with better financial reporting practices and a reduced likelihood of financial reporting scandals. The study concludes that robust internal control systems are critical to preventing financial reporting irregularities and recommends that NSE-listed companies’ boards of directors, audit committees, and regulatory authorities, such as the Capital Markets Authority, prioritize strengthening internal control frameworks to enhance financial reporting integrity.